On the experimental value of the ∆⁺ (1232) mass from γp→nπ⁺ (pπ⁰ ) reactions - Omelaenko, A.S. (Вопросы атомной науки и техники, 2002)
The reliability of the phenomenological estimates for the D⁺(1232) mass is questioned coming from the of π⁺ and π⁰ mesons photoproduction data off proton target till the end of 2001. The origin of an old discrepancy for the D⁺(1232) mass presented in tables of the Particle Data Group is discussed.